2015
DOI: 10.3390/rs71215858
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Chemical Vapour Detection by Micro UAV

Abstract: Abstract:The ability to remotely detect and map chemical vapour clouds in open air environments is a topic of significant interest to both defence and civilian communities. In this study, we integrate a prototype miniature colorimetric chemical sensor developed for methyl salicylate (MeS), as a model chemical vapour, into a micro unmanned aerial vehicle (UAV), and perform flights through a raised MeS vapour cloud. Our results show that that the system is capable of detecting MeS vapours at low ppm concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…On this basis, the most suitable drone is a rotary wing. Numerous previous studies have shown that this configuration provides the right balance between the desired requirements [1,2,5].…”
Section: Application In Case Of a Cbrn Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, the most suitable drone is a rotary wing. Numerous previous studies have shown that this configuration provides the right balance between the desired requirements [1,2,5].…”
Section: Application In Case Of a Cbrn Eventmentioning
confidence: 99%
“…The aerial platform may be equipped with a variety of sensors, capable of investigating and discriminating the nature of the threat for several classes of chemical and radiological contaminants. Some groups have reported the use of gas sensors mounted on a drone [1]. Different approaches have been compared for gas release localization with mobile platforms, and gas sensing systems have been developed and tested specifically for Volatile Organic Chemicals (VOC) [2] and Chemical Warfare Agents (CWAs) [3] localization and mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Inevitably, drones leaked out to other sectors, and have become affordable enough for commercial and research use to undertake certain tasks that were once difficult to carry out using conventional approaches (West, 2015). It is far safer and cheaper to employ drones for inspection and monitoring of remote infrastructure and hazardous places than to utilize a person (Rosser et al, 2015). For example, the oil industry is using drones to inspect oil pipelines and oilrigs.…”
Section: Introductionmentioning
confidence: 99%
“…Hazards to equipment and personnel can also be minimized by the mobility of the UAS as well as their ability to be remotely operated away from hazardous sources. UAS-based emission samplers have been used for measurement of area source gases (Neumann et al, 2013;Rosser et al, 2015;Chang et al, 2016;Li et al, 2018), point source gases (Villa et al, 2016), aerosols (Brady et al, 2016), black carbon particles (Craft, 2014), volcanic pollutants (Mori et al, 2016), particle mass (Peng et al, 2015), and particle number concentrations (Villa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%